2022
DOI: 10.1007/s10055-022-00733-4
|View full text |Cite
|
Sign up to set email alerts
|

Dropout rate in randomised controlled trials of balance and gait rehabilitation in multiple sclerosis: is it expected to be different for virtual reality-based interventions? A systematic review with meta-analysis and meta-regression

Abstract: To assess and meta-analyse the pooled dropout rate from the randomised control trilas that use virtual reality for balance or gait rehabilitation in people with multiple sclerosis. A systematic review of randomised control trials with meta-analysis and meta-regressions was performed. A search was conducted in PubMed, Scopus, Web of Science, the Physiotherapy Evidence Database, the Cochrane Database, CINHAL, LILACS, ScienceDirect, and ProQuest. It was last updated in July 2022. After the selection of studies, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Therefore, the future research agenda should analyze the efficacy of telerehabilitation in more severely affected patients and increase the panel typology of treatments delivered remotely for complete physical and cognitive telerehabilitation in patients with chronic neurological diseases. Furthermore, the observed dropout rate (slightly more than 10%) was higher than the estimated a priori dropout rate (about 5%), approximately expected in these two neurological populations after virtual reality clinical trials as reported from recent metanalyses [86,87]. In these metanalyses, the typical reasons for dropout were difficulties in reaching the research center, refusal to participate, personal or familial issues, loss of data due to administrative problems, exacerbation of symptoms or other medical complications [86].…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the future research agenda should analyze the efficacy of telerehabilitation in more severely affected patients and increase the panel typology of treatments delivered remotely for complete physical and cognitive telerehabilitation in patients with chronic neurological diseases. Furthermore, the observed dropout rate (slightly more than 10%) was higher than the estimated a priori dropout rate (about 5%), approximately expected in these two neurological populations after virtual reality clinical trials as reported from recent metanalyses [86,87]. In these metanalyses, the typical reasons for dropout were difficulties in reaching the research center, refusal to participate, personal or familial issues, loss of data due to administrative problems, exacerbation of symptoms or other medical complications [86].…”
Section: Discussionmentioning
confidence: 66%
“…Not only apps measuring fatigue through questionnaires but also wearable devices have proved to be useful in the continuous monitoring of fatigued MS patients (Sparaco et al, 2018;Tong et al, 2019;Block et al, 2022). These "health technologies" usually have an internet or smartphone connection and therefore allow non-stop collection of data about physiological parameters (e.g., heart rate, sleep levels) and track any kind 2019;Maggio et al, 2019a,b;Cuesta-Gómez et al, 2020;Manuli et al, 2020;Ozkul et al, 2020;Yazgan et al, 2020;Cortés-Pérez et al, 2021;Leonardi et al, 2021;Nascimento et al, 2021;Pagliari et al, 2021;Altunkaya et al, 2022;Casuso-Holgado et al, 2022;Hollywood et al, 2022;Kalron et al, 2022;Moeinzadeh et al, 2022;Dogan et al, 2023;Hsu et al, 2023) Computer of physical activities through accelerometers and sensors (Sparaco et al, 2018).…”
Section: Wearable Devicesmentioning
confidence: 99%
“…Some studies have hinted at the fact that a longer duration of the rehabilitation program could cause fatigued patients with MS to lose motivation and thus adherence. Consensus about the right duration of a VR therapy session is one more time difficult to find in the literature, but it is strategic to keep in mind the potential obstacles of VR, which can hinder efficacy and cost-effectiveness (Bevens et al, 2022;Casuso-Holgado et al, 2022). Manuli et al viewed a possible solution to this gap by adding the patients' reported opinions and outcomes to the concept of feasibility.…”
Section: Virtual Realitymentioning
confidence: 99%
“…Some studies have hinted at the fact that a longer duration of the rehabilitation program could cause fatigued patients with MS to lose motivation and thus adherence. Consensus about the right duration of a VR therapy session is one more time difficult to find in the literature, but it is strategic to keep in mind the potential obstacles of VR, which can hinder efficacy and cost-effectiveness (Bevens et al, 2022 ; Casuso-Holgado et al, 2022 ). Manuli et al viewed a possible solution to this gap by adding the patients' reported opinions and outcomes to the concept of feasibility.…”
Section: The Concept Of Digital Assessment and Management Of Multiple...mentioning
confidence: 99%
“…Not only apps measuring fatigue through questionnaires but also wearable devices have proved to be useful in the continuous monitoring of fatigued MS patients (Sparaco et al, 2018;Tong et al, 2019;Block et al, 2022). These "health technologies" usually have an internet or smartphone connection and therefore allow non-stop collection of data about physiological parameters (e.g., heart rate, sleep levels) and track any kind Manuli et al, 2020;Ozkul et al, 2020;Yazgan et al, 2020;Cortés-Pérez et al, 2021;Leonardi et al, 2021;Nascimento et al, 2021;Pagliari et al, 2021;Altunkaya et al, 2022;Casuso-Holgado et al, 2022;Hollywood et al, 2022;Kalron et al, 2022;Moeinzadeh et al, 2022;Dogan et al, 2023;Hsu et al, 2023) Computer of physical activities through accelerometers and sensors (Sparaco et al, 2018).…”
Section: Wearable Devicesmentioning
confidence: 99%